2020
DOI: 10.1177/1363460719888432
|View full text |Cite
|
Sign up to set email alerts
|

Sex and relationships education for LGBT+ young people: Lessons from UK youth work

Abstract: Lesbian, gay, bisexual and trans (LGBT) inclusive sex and relationships education (SRE) is of growing interest. However, there is a lack of clarity about what LGBT inclusive SRE should/does look like in practice. This article addresses that uncertainty by examining original research findings on innovative youth work based SRE provided within an arts-based project run by a third sector organisation in the North East of England. The research is set within the context of three broad rationales for LGBT inclusive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…This can reinforce heteronormative ideas of sex (Hirst, 2008) and may consequently lead to the deligitimization of same-sex /gender experiences as reported by our sample. As the recentlyimplemented UK Relationships and Sex Education (RSE) curriculum is enacted, it will be important to evaluate whether it has the intended effect of increasing inclusivity and improving sexual self-efficacy for all students (Formby & Donovan, 2020;Pound et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can reinforce heteronormative ideas of sex (Hirst, 2008) and may consequently lead to the deligitimization of same-sex /gender experiences as reported by our sample. As the recentlyimplemented UK Relationships and Sex Education (RSE) curriculum is enacted, it will be important to evaluate whether it has the intended effect of increasing inclusivity and improving sexual self-efficacy for all students (Formby & Donovan, 2020;Pound et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, expressions of LGB+ sexuality are underrepresented in the media and narratives including LGB+ individuals are often restricted to jokes and coming-out stories; characters also tend to be primarily adult gay men (Bond et al, 2019;Fisher et al, 2007). Additionally, there has also been a lack of LGB+ content within UK schools' SRE (Formby & Donovan, 2020;Pound et al, 2017) which has been shown to play a key role in reinforcing heteronormative ideas of sex (Hirst, 2008). As a result, culturally informed sexual scripts are less available for same-sex/gender sex and relationships, particularly among adolescents and young adults, and LGB+ couples have reported feeling as though they have no "normal" on which to base their relationships (Greene et al, 2015).…”
Section: Sexual Scriptsmentioning
confidence: 99%
“…This could be said for many women experiencing domestic abuse in relationships, but is confounded further within homosexual relationships due to the absence of established norms within a healthy same-sex relationship (Grant & Nash, 2018). Formby and Donovan (2020) reiterate these findings, reporting that a quarter of the young people they surveyed knew of LGBTQ friends who had been in an abusive relationship. They felt this was due to the narrative of domestic abuse as a heterosexual problem, perpetrated only by men, leaving out descriptions of coercive control or emotional abuse.…”
Section: Narrative Synthesis Resultsmentioning
confidence: 85%
“… 15 25 35 However, two studies noted caution surrounding online sexual health education due to the propensity of some to use pornography as a form of education tool. 24 25 …”
Section: Resultsmentioning
confidence: 99%